Utilização do software FreeMat no ensino de funções, matrizes e sistemas lineares no ensino médio - Cardoso, Fernando Henrique (2015)
This work presents some pedagogical approaches to teaching mathematics using the FreeMat software. The approaches are characterized as methodological proposals for activities to be developed and applied in teaching functions, matrices and linear systems. The aim is to facilitate the learning of these contents, by the students of high school, through the application of computational resource.